1994
DOI: 10.1007/bf00126743
|View full text |Cite
|
Sign up to set email alerts
|

The development of a simple empirical scoring function to estimate the binding constant for a protein-ligand complex of known three-dimensional structure

Abstract: A new simple empirical function has been developed that estimates the free energy of binding for a given protein-ligand complex of known 3D structure. The function takes into account hydrogen bonds, ionic interactions, the lipophilic protein-ligand contact surface and the number of rotatable bonds in the ligand. The dataset for the calibration of the function consists of 45 protein-ligand complexes. The new energy function reproduces the binding constants (ranging from 2.5.10(-2) to 4.10(-14) M, corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
533
1
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 977 publications
(543 citation statements)
references
References 65 publications
5
533
1
4
Order By: Relevance
“…Molecular dynamics simulations including the explicit treatment of solvent molecules have encountered a number of striking successes (see, e.g., Bash et al, 1987;McCammon, 1987;Beveridge & DiCapua, 1989;Straatsma & McCammon, 1991;Miyamoto & Kollman, 1993;Kollman, 1993Kollman, , 1994; however, the need to sample a large ensemble of conformational states places severe computational demands on this approach. At the other extreme, a variety of empirical methods have also been developed to estimate binding free energies (see, e.g., Andrews et al, 1984;Williams et al, 1991Williams et al, , 1993Bohm, 1994). These methods, which, for example, assign a free energy value to each hydrogen bond, salt bridge, and buried nonpolar area, provide extremely useful qualitative tools.…”
mentioning
confidence: 99%
“…Molecular dynamics simulations including the explicit treatment of solvent molecules have encountered a number of striking successes (see, e.g., Bash et al, 1987;McCammon, 1987;Beveridge & DiCapua, 1989;Straatsma & McCammon, 1991;Miyamoto & Kollman, 1993;Kollman, 1993Kollman, , 1994; however, the need to sample a large ensemble of conformational states places severe computational demands on this approach. At the other extreme, a variety of empirical methods have also been developed to estimate binding free energies (see, e.g., Andrews et al, 1984;Williams et al, 1991Williams et al, , 1993Bohm, 1994). These methods, which, for example, assign a free energy value to each hydrogen bond, salt bridge, and buried nonpolar area, provide extremely useful qualitative tools.…”
mentioning
confidence: 99%
“…Recently empirical and knowledge-based scoring functions have been developed. Böhm et al reported that the score value calculated by the Ludi program well approximated the binding affinity [8,9]. In one of their studies, a correlation with a standard deviation of 1.7 kcal/mol (number of structures = 82, correlation coefficient = 0.89) was obtained between the experimental and calculated binding free energies derived from K i values.…”
Section: Score Calculationmentioning
confidence: 96%
“…The score value was reported to correspond to the dissociation constant K i by Böhm et al [8] [9]. They derived the empirical parameters of the score function from the protein-ligand complexes of known 3D structure in the Protein Data Bank [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three types of scoring functions are currently applied in currently available docking programs. These scoring functions are based on: force field [41,42], empirical approaches [43,44] and knowledge based [45,46]. Discriminating or predictive power of these functions have high influence on an outcome of any docking protocol.…”
Section: /7mentioning
confidence: 99%